VD_FINDINFO Décision / 2014 / 876 vom 20. Oktober 2014 - VD Tribunal cantonal (2014)
RADIATION DU RÔLE, RENONCIATIONSENS GÉNÉRAL, VOLONTÉ DE RECOURIR | 38 al. 2bis LPGA, 79 LPA-VD, 94 al. 1 let. c LPA-VD